The Impact of Mismatch Repair Status on Prognosis of Patients With Gastric Cancer: A Multicenter Analysis - Guan, Wen-Long; Ma, Yue; Cui, Yue-Hong; Liu, Tian-Shu; Zhang, Yan-Qiao; Zhou, Zhi-Wei; Xu, Jian-Ying; Yang, Li-Qiong; Li, Jia-Yu; Sun, Yu-Ting; Xu, Rui-Hua; Wang, Feng-Hua; et al. (Frontiers in Oncology, 2021)
Background The clinical role of deficient DNA mismatch repair (dMMR)/microsatellite instability-high (MSI-H) in gastric cancer (GC) is still controversial. We aimed to analyze the relationship between dMMR/MSI-H and clinicopathological features along with survival. Methods Patients who were diagnosed with GC at the three big cancer centers in China from 2015 to 2020 were evaluated retrospectively. MMR/MSI status was assessed using immunohistochemistry/PCR. Clinical and pathological data were collected from the medical record system. Results A total of 196 patients with dMMR/MSI-H status were enrolled for analysis. The prevalence of MSI-H/dMMR in GC was 6.6%. Another 694 proficient MMR (pMMR) GC patients were enrolled for comparison. Compared with pMMR patients, dMMR/MSI-H patients were associated with older age, female predominance, distal location in the stomach, earlier TNM stage, intestinal subtype, better differentiation, and more negative HER2 status. The median overall survival (OS) of the dMMR/MSI-H group was better than that of the pMMR/microsatellite stability (MSS) group (not reached vs. 53.9 months, p = 0.014). Adjuvant chemotherapy had no impact in both disease-free survival (DFS) and OS of dMMR/MSI-H patients (p = 0.135 and 0.818, respectively). dMMR/MSI-H patients had poorer response and progression-free survival (PFS) of first-line chemotherapy, though they were statistically significant (p = 0.361 and 0.124, respectively). Conclusions dMMR/MSI-H GC patients have specific clinicopathological characteristics and better prognosis than pMMR patients.